Intel® Geek Kids @N9: UiTM and Penang Science Cluster (PSC) empowering communities through collaboration / Haslinda Noradzan ... [et al.] - Noradzan, Haslinda; Wan Ghani, Wan Aryati; Mohd Yunus, Sri Yusmawati; Md Sarif, Shamsudin (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Intel Malaysia has initiated the Intel® Geek Kids (IGK) programme in partnership with the Penang Science Cluster (PSC) to encourage Science, Technology, Engineering, and Mathematics (STEM) education among students in primary schools located in rural areas in Malaysia. Following a successful pilot program in 2022, the initiative aims to foster interest in STEM through workshops and competitions. For young learners in Malaysia, the programme seeks to promote interest, empower students, and build a bright future with countless prospects in STEM fields.